Distribuição espaço-temporal de esteróis e hormônios estrógenos e o seu potencial toxicológico no sedimento do rio Jaguaribe/CE - Morais, Pollyana Cristina Vasconcelos de (2018)
The Jaguaribe River has the largest drainage basin in the state of Ceará, occupying 50% of the state and thereby it is influenced by multiple sources of contamination. The contribution of effluents is the largest source of contaminants for aquatic environments, due to its volume and its lack of treatment. Therefore, it causes negative effects to the balance of the ecosystem and affects public health. The quality of the sediment of the Jaguaribe River was evaluated by identification and quantification of sterols and estrogen hormones. To do this, a multiresidue extraction method was optimized, tested, and validated, followed by gas chromatographic analysis. Finally, ecotoxicological tests were carried out in order to analyze the toxic conditions of both sampled sediments and synthetic estrogen hormones. Looking into superficial sediment, COP was not the most evident sterol, representing 4,8% of total sterols. On the other hand, COL and COLN, which can also be associated with sewage, represented 21,1% and 8,8% of total sterols in all sampling sites, respectively. Based on the sterol diagnostic ratios, superficial sediments were classified as contaminated. Regarding to estrogen hormones, sum of synthetic compounds (ΣSynthetic) were predominant for the constitution of the total sum of hormones ( Σtotal) in superficial sediments. They represented 76,6% of Σtotal, while sum of natural compounds (ΣNature) were responsible for 23,5%. In respect of the two sediment cores, each of them were fractioned in 10 sections which were dated. Sediment core TJ1 temporal variation was from 1937 to 2002, while sediment core TJ2 temporal variation was from 1947 to 2003. ESTIG was the predominant sterol in these sediments, which is characteristic of biogenic contribution. Based on the sterol diagnostic ratios, TJ1 was considered contaminated for every fraction, while TJ2 presented two uncontaminated fractions. Related to synthetic estrogen hormones, EE2 was the most abundant in the two sediment cores. Ecotoxicological analysis showed points PJ1, PJ2, PJ4, PJ9, PJ10, PJ12, and PJ14 as toxic in the tests performed. In the spiked test, synthetic estrogen hormones were toxic at the exposed concentrations (1, 10, 100 ng/g), only EE2 showed no toxicity at concentrations 1 and 2.5 ng/g. Based on all these evidences, it can be stated that there are effluents from many forms of use and occupation of the medium and low Jaguaribe.